The Wehrmacht Retreats : Fighting a Lost War, 1943 - Citino, Robert Michael, 1958- (Book collections on Project MUSE., 2012)
"Throughout 1943, the German army, heirs to a military tradition that demanded and perfected relentless offensive operations, succumbed to the realities of its own overreach and the demands of twentieth-century industrialized warfare. In his new study, prizewinning author Robert Citino chronicles this weakening Wehrmacht, now fighting desperately on the defensive but still remarkably dangerous and lethal. Drawing on his impeccable command of German-language sources, Citino offers fresh, vivid, and detailed treatments of key campaigns during this fateful year: the Allied landings in North Africa, General von Manstein's great counterstroke in front of Kharkov, the German attack at Kasserine Pass, the titanic engagement of tanks and men at Kursk, the Soviet counteroffensives at Orel and Belgorod, and the Allied landings in Sicily and Italy. Through these events, he reveals how a military establishment historically configured for violent aggression reacted when the tables were turned; how German commanders viewed their newest enemy, the U.S. Army, after brutal fighting against the British and Soviets; and why, despite their superiority in materiel and manpower, the Allies were unable to turn 1943 into a much more decisive year."--Page 2 of cover.